2003
DOI: 10.1590/s0103-64402003000100005
|View full text |Cite
|
Sign up to set email alerts
|

Salivary characteristics of diabetic children

Abstract: Salivary components may suffer variations that can be detected by chemical determinations. The aim of this work was to determine physical and biochemical characteristics of the saliva of a group of diabetic children compared to those of a control group. Relation to oral health indices was also determined. Twenty diabetic children (3-15-years-old) and 21 control children (5-12-years-old) were included in this study. Total proteins, sugars and calcium were determined by colorimetric methods, and glucose, urea, α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
136
5
26

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(196 citation statements)
references
References 13 publications
29
136
5
26
Order By: Relevance
“…Several investigators found that, on average, after 20 days of effective diabetic state both chemically induced diabetic rats and autoimmune diabetic mice showed a reduction in submandibular gland weight, a decrease in granular ducts and in the density of secretory granules, and accumulation of lipid droplets in acini and intercalated ducts, in addition to growth retardation of the parotid and submandibular glands (Anderson, 1983;High et al, 1985;Hu et al, 1992;Anderson et al, 1994;Leigh et al, 1994). Furthermore, clinical and experimental studies have demonstrated a reduction in secretory and salivary components, as well as a severe inflammatory reaction accompanied by the presence of mononuclear cells first located around blood vessels and then around acini and ducts (Goillot et al, 1991;Hu et al, 1992;Pozzilli et al, 1993;Humphreys-Beher et al, 1998;Yamano et al, 1999;López et al, 2003). Differences in the tissue responses between parotid and submandibular glands have already been reported for chemically induced diabetic rats, mainly in terms of parotid gland weight, which did not show significant alterations (Anderson and Johnson, 1981).…”
Section: Discussionmentioning
confidence: 96%
“…Several investigators found that, on average, after 20 days of effective diabetic state both chemically induced diabetic rats and autoimmune diabetic mice showed a reduction in submandibular gland weight, a decrease in granular ducts and in the density of secretory granules, and accumulation of lipid droplets in acini and intercalated ducts, in addition to growth retardation of the parotid and submandibular glands (Anderson, 1983;High et al, 1985;Hu et al, 1992;Anderson et al, 1994;Leigh et al, 1994). Furthermore, clinical and experimental studies have demonstrated a reduction in secretory and salivary components, as well as a severe inflammatory reaction accompanied by the presence of mononuclear cells first located around blood vessels and then around acini and ducts (Goillot et al, 1991;Hu et al, 1992;Pozzilli et al, 1993;Humphreys-Beher et al, 1998;Yamano et al, 1999;López et al, 2003). Differences in the tissue responses between parotid and submandibular glands have already been reported for chemically induced diabetic rats, mainly in terms of parotid gland weight, which did not show significant alterations (Anderson and Johnson, 1981).…”
Section: Discussionmentioning
confidence: 96%
“…La diminution de la sécrétion salivaire est l'une des principales conséquences du diabète insulino-dépendant de type I chez l'enfant. Lopez et al [5] et Wu et al [12] ont montré que les enfants diabétiques présentent une fréquence carieuse plus importante que les enfants non diabétiques, une augmentation du taux de glucose salivaire, une hyposialie et une diminution du pH salivaire ; Wu et al [12] ont souligné que la salive constitue un élément important pour le maintien d'une bonne santé bucco-dentaire. La carie est une maladie infectieuse dont l'apparition est favorisée par un taux anormalement élevé de certaines bactéries, plus particulièrement les Streptocoques mutans et les lactobacilles qui sont respectivement impliqués dans l'initiation de la lésion carieuse et dans sa progression.…”
Section: Résultats Discussionunclassified
“…The main objective of this procedure is to investigate the presence of hyposalivation which can be caused by various etiologic factors such as: head and neck radiotherapy (2), intake of medications (3), schizophrenia (4), Sjögren's syndrome (5) and diabetes mellitus (6)(7). Besides the reduction in salivary flow causing dry mouth, burning mouth and taste disturbance (8), the quality of saliva shows a shift towards a more acidogenic microflora (1).…”
Section: Introductionmentioning
confidence: 99%